Robust Stability of Implicit Dynamic Equations on Time Scales - Ha, Nguyen Thu (VNU Journal of Science: Mathematics - Physics, 2019)
This paper studies the robust stability of implicit dynamic equations on time scales, which is a general form of differential algebraic equations and implicit difference equations. The paper discusses the reservation of exponential stability of these equations under small Lipschitz perturbations.